Measurement of CO2 adsorption kinetics on activated carbons suitable for gas storage systems. Issue 1 (25th October 2016) - Singh, Vinod Kumar; Kumar, E. Anil
Abstract: The adsorption kinetics of CO2 on three commercially available activated carbons namely Norit RB3 (steam activated rod) (RB3), Norit Darco 100 mesh size (Darco 100 mesh), and Norit Darco 12 × 20 US mesh size (Darco 12 × 20) are measured using Sievert's apparatus at different supply pressures (1, 5, 10, and 20 bar) and temperatures (298, 308, 318, and 338 K). Extracts of experimental results of CO2 adsorption kinetics are used for mathematical modelling using different standard models, such as pseudo‐first order, pseudo‐second order, Elovich, and intra‐particle diffusion kinetics models. The adsorbate‐adsorbent interactions and kinetics behavior of CO2 adsorption on adsorbents are deduced from the best‐fitted kinetics model. Based on coefficient of correlation and normalized standard deviation, it has been found that pseudo‐second order kinetics model very well suits with the experimental data of CO2 adsorption kinetics. Activation energies at different pressures are calculated by fitting the Arrhenius equation to the adsorption kinetics data. Analysis of the mechanism of interaction between CO2 molecules and adsorbents during the adsorption process is attempted using interparticle and Boyd's diffusion models. It has been found that the film‐diffusion is an important rate controlling step in CO2 adsorption process. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd.